"Courts of Conscience": Local Law, the Baptists, and Church Schism in Kentucky, 1780–1840. Issue 1 (5th March 2015) - Unknown
Abstract : This article examines how religious controversy affected antebellum Kentucky's legal culture and helped construct the relationship between church and state. It incorporates legal theory to broaden conceptions of law and argues that Baptist churches served as important legal sites for their communities. More than simply punishing moral transgressions, churches litigated disputes that under common law and within county courts would be considered criminal or civil law. By acknowledging that individuals produced law outside of state institutions, the article illuminates a more complex and fluid trans-Appalachian legal culture, one in which church members and non-members alike possessed a capacious vision of law. During the late 1820s and 1830s, Kentucky Baptists faced years of discord emanating from Alexander Campbell's "Reformation." Amidst a religious backdrop of doctrinal controversy and schism, afflicted churches witnessed a decline of disciplinary activities as individuals' ceased to envision their churches as sites for neutral dispute resolution. The failure of church courts to contain internal dissension and curtail schism led to contentious court battles over rights to local meetinghouses. As judges reviewed church disciplinary records and litigants debated religious doctrine at the courthouse, these church property disputes highlight the process of redefining church-state relations in the post-establishment era.